A Critical Architecture – Comments on Politics and Society. (December 2012) - Frampton, Kenneth; Cairns, Graham
Abstract : Over a fifty year career as an architectural critic and historian Kenneth Frampton has consistently defended the Modernist agenda of the Twentieth Century. However, he has also been fiercely critical of its failings and shortcomings. He has taught at the world's most prestigious institutions, produced a body of work that can be defined as kaleidoscopic and has written texts which have become part of the canon of architectural history and theory. His encyclopedic Modern Architecture: a Critical History, is in its fourth edition and still remains a bedrock text for our understanding of the Modern Movement more than twenty years after its initial publication. His ground-breaking essay of 1983, Towards a Critical Regionalism: Six Points for an Architecture of Resistance set the agenda for a reconsideration of Modernism that continues to resonate today. He has published internationally on a whole range of issues and remains committed to a critical analysis of Modernism which places architecture firmly in the context of the social and political milieu of the left. In this fifty year career, the ideas of the social and political theorist Hannah Arendt have operated as a form of conceptual and ethical foundation. His 1979 essay, The Status of Man and the Status of his Objects, is a form of analysis of her theories that explores, amongst other things, her distinction between work and labour in the specific context of architecture. This essay is also given primary importance in his 2002 book Labour, Work and Architecture: Collected Essays on Architecture and Design, which he dedicates to the memory of Arendt. In his 1979 essay, he suggests that reading Arendt's work in 1965 illuminated the "invariably confusing distinction between building (as process) and architecture (as stasis)", with architecture having as its primary charge the creation of the public realm. He begins this interview-article by summarising these themes, but also by drawing out the relevance of Arendt's ideas in the context of contemporary commodified culture. He goes on to explore a whole range of other ideas including the mediatisation of architecture, high rise development, suburbia and the role of government in the architecture of the United States and the United Kingdom.